2021
DOI: 10.5812/jjm.112486
|View full text |Cite
|
Sign up to set email alerts
|

Co-occurrence of Carbapenemase-encoding Genes Among Klebsiella pneumoniae Clinical Isolates: Positive Relationship of bla NDM and bla SIM with Imipenem Resistance

Abstract: Background: Carbapenem-resistant Klebsiella pneumoniae (CR-KP), known as a significant public health threat, is the most common causative agent of nosocomial and community-acquired infections. Objectives: This study aimed to evaluate resistance to carbapenems and determine the prevalence of carbapenemase genes and multilocus sequence typing (MLST) of K. pneumoniae clinical isolates. Methods: One-hundred K. pneumoniae isolates were evaluated. The minimum inhibitory concentrations (MIC) of imipenem and meropenem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 34 publications
1
2
1
Order By: Relevance
“…Although many previous studies [47][48][49] have reported that bla NDM is the main mechanism of carbapenem resistance in Gram-negative bacteria including K. pneumoniae, this study showed a clear correlation between carrying the bla OXA-48 gene and imipenem resistance (with p values of < 0.014). Consequently, the bla OXA-48 gene may play a significant role in carbapenem resistance, but other factors such as deficiency or decreased expression of porins and increased activity of bacterial efflux pump need to be considered.…”
Section: Discussioncontrasting
confidence: 81%
“…Although many previous studies [47][48][49] have reported that bla NDM is the main mechanism of carbapenem resistance in Gram-negative bacteria including K. pneumoniae, this study showed a clear correlation between carrying the bla OXA-48 gene and imipenem resistance (with p values of < 0.014). Consequently, the bla OXA-48 gene may play a significant role in carbapenem resistance, but other factors such as deficiency or decreased expression of porins and increased activity of bacterial efflux pump need to be considered.…”
Section: Discussioncontrasting
confidence: 81%
“…The results obtained among KPC producing K. pneumoniae also reflect the well-known dominance of ST258 clone in USA (100). Multilocus sequence typing in carbapenem-resistant K. pneumoniae strains showed that ST15 was prevalent in Portugal (4), ST395 in France (69), ST11 in China (106,107), and ST14, ST5188, ST1861 in Iran (98).…”
Section: Genetic Diversity Of Antibiotic Resistant Isolatessupporting
confidence: 64%
“…The most frequent antibiotic resistance genes, such as genes coding the production of ESBL, are located in plasmids. Recent studies point to plasmid-mediated transfer in hospitals in Africa (17, 19, 25-28, 33, 52, 101), Asia (35,40,42,45,57,94,98,105), Latin America (63-65), Europe (67,72,91), and North America (89,100,103).…”
Section: Distribution Of Antibiotic Resistance Genes (Arg)mentioning
confidence: 99%
“…However, the overuse of carbapenems in hospitals has led to an increase in Carbapenem-Resistant Klebsiella pneumoniae (4). Klebsiella pneumoniae carbapenemase (KPC)-producing is becoming distressing (5). Several mechanisms result in resistance to carbapenems, including the production of carbapenemases of class A (KPC, GES, and others), class B (mainly IMP, VIM, or NDM), and class D (OXA-48) and related enzymes.…”
Section: Introductionmentioning
confidence: 99%